2013
DOI: 10.1016/j.vaccine.2013.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to oral rabies vaccination in raccoon kits: Problems and implications

Abstract: Little is known about the immunogenicity of RABORAL V-RG(®) (V-RG), an oral rabies vaccine, in raccoon kits (Procyon lotor). The objectives of this study were to characterize the immunogenicity of V-RG in young kits and investigate the potential impact of maternal antibodies on response to vaccination of nursing raccoon kits. Raccoon kits (n=30) were vaccinated at either 3 weeks of age, 7 weeks of age, or assigned as contact controls. Nineteen kits (73%) that were whelped by unvaccinated mothers responded to V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Our simulations show seasonal disease dynamics driven by the influx of susceptible juveniles during the synchronous birth pulse in early April to mid‐May. Spring vaccination was less effective because it coincides with this birth pulse, when susceptible juveniles are not yet weaned and are unlikely to forage for and ingest oral vaccine baits (Fry et al, ). Fall vaccination was more effective because susceptible juveniles—who otherwise may have been infectious or incubating the virus—were immunized prior to natal dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…Our simulations show seasonal disease dynamics driven by the influx of susceptible juveniles during the synchronous birth pulse in early April to mid‐May. Spring vaccination was less effective because it coincides with this birth pulse, when susceptible juveniles are not yet weaned and are unlikely to forage for and ingest oral vaccine baits (Fry et al, ). Fall vaccination was more effective because susceptible juveniles—who otherwise may have been infectious or incubating the virus—were immunized prior to natal dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…This bait timing is also advantageous because maternal antibodies in juveniles would have waned by this time. Fry et al [58] estimated the half-life of maternal antibodies to be 10.5 days post-weaning, and the results of this study also suggested (although not definitively) that the presence of maternal antibodies could interfere with a young raccoon’s ability to properly respond to oral vaccination. Similarly, juvenile foxes demonstrated an impaired immune response during a challenge with RABV, even after maternal antibodies were no longer detected [60].…”
Section: Rabies Management Strategiesmentioning
confidence: 49%
“…Juveniles are an important cohort to target, given that they represent a pulse of new susceptible individuals that are capable of driving transmission dynamics. During this time of year, natural food resources might become more limited, which increases the attractiveness of baits, and the vaccine baits are less likely to be impacted by extreme temperatures [58, 59]. This bait timing is also advantageous because maternal antibodies in juveniles would have waned by this time.…”
Section: Rabies Management Strategiesmentioning
confidence: 99%
“…In another case, two adult raccoons housed with orally immunized cage mates developed low levels of RVNA and also survived rabies virus challenge [ 52 ]. Finally, half of non-vaccinated raccoons in contact with raccoons kits orally vaccinated with V-RG (10 8.2 PFU/animal) developed detectable RVNA, suggesting the possibility of limited horizontal vaccine transmission among kits through suckling or playing immediately after oral vaccination [ 57 ].…”
Section: V-rg Vaccine Safetymentioning
confidence: 99%
“…All animals remained healthy, seroconverted within 28 days, and resisted rabies virus challenge [ 52 ]. V-RG has also been administered orally to 3 to 7 weeks old raccoon kits without adverse events [ 57 ].…”
Section: V-rg Vaccine Safetymentioning
confidence: 99%